Review of the grass-feeding leafhopper genera Miradeltaphus Dash & Viraktamath and Yuanamia Zhang & Duan (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) - Duan, Yani; Dietrich, Christopher H.; Zhang, Yalin (Zootaxa, 2016)
Miradeltaphus Dash & Viraktamath and Yuanamia Zhang & Duan are revised, one new species M. sanogae sp. n. is described and Parayuanamia Xing & Li is considered a junior synonym of Yuanamia Zhang & Duan syn. n. Both genera are newly recorded from Thailand. A revised key to the Palearctic and Oriental genera of Deltocephalini is provided.